Highly flexible and fitted earmuff and preparation method thereof
By adopting a combination design of the outer protective layer, sound absorbing layer and flexible layer in the earmuffs, the existing earmuff products ignore comfort and other quality when pursuing sound insulation effects, achieving excellent sound insulation effects and high comfort earmuff products.
Patent Information
- Application Number
- CN202411975296.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing earmuff products ignore comfort and other quality of use when pursuing sound insulation, resulting in uncomfortable wearing and poor sound insulation. The problem is even more prominent when worn for a long time.
It adopts a highly flexible fit ear cup design composed of an outer protective layer, a sound absorbing layer and a flexible layer. The outer protective layer is a mixed fiber of polyester fiber and nylon fiber. The sound absorbing layer contains modified fibers to improve mechanical, waterproof and corrosion resistance. The flexible layer is composed of polyether polyols, polyisocyanates and other materials.
It achieves excellent sound insulation, while ensuring the high moisture resistance, water resistance, aging resistance and mechanical quality of the earmuffs, which is suitable for long-term wear environments such as music production and industrial operations.
Abstract
Description
Technical Field
[0001] The present application relates to the field of earmuff products, and in particular to a highly flexible and fitted earmuff and a preparation method thereof. Background Art
[0002] With the development of science and technology and the improvement of people's living standards, the demand for personal hearing protection is increasing. Especially when working or entertaining in a noisy environment, such as music production, industrial production and other occasions, high-quality earmuffs have become an indispensable equipment. Although traditional earmuffs can provide sound insulation to a certain extent, due to material limitations, they often have problems such as poor wearing comfort and poor sound insulation. These problems are particularly prominent for long-term wear. Therefore, the development of an earmuff with both excellent sound insulation performance and high comfort has become an urgent market demand.
[0003] However, in order to pursue more sound insulation effect, the existing earmuff products further ignore the comfort and other use qualities of the earmuffs, such as the softness, fit, aging resistance, moisture resistance, water resistance and corrosion resistance of the earmuffs, etc. This greatly affects the overall quality of the earmuff products and reduces their use effect in actual application.
[0004] Therefore, in order to effectively solve the above-mentioned technical problems and meet the existing market demand, the present application provides a highly flexible and fitted earmuff and a preparation method thereof. The earmuff product prepared by the present application not only has excellent sound insulation effect, but also can effectively ensure that it has good moisture-proof, water-resistant, aging-resistant and mechanical quality properties, and is especially suitable for environments that require long-term wearing, such as music production, industrial operations and other fields. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a highly flexible and fit earmuff, the structure of which includes an outer protective layer at the top, a sound absorbing layer in the middle and a flexible layer at the bottom.
[0006] As a preferred solution, the thickness of the outer protective layer is 1-2 mm.
[0007] As a preferred solution, the thickness of the sound absorbing layer is 3-5 mm.
[0008] As a preferred solution, the thickness of the flexible layer is 5-10 mm.
[0009] As a preferred solution, the outer protective layer is a mixed fiber of polyester fiber and nylon fiber.
[0010] As a preferred solution, the mass ratio of the polyester fiber to the nylon fiber is 1-1.5:1.
[0011] As a preferred solution, the raw materials of the flexible layer are, by mass, 30-40 parts of polyether polyol, 20-30 parts of polyisocyanate, 5-10 parts of foaming agent, 1-2 parts of catalyst, 1-2 parts of stabilizer, 3-5 parts of flame retardant, 1-2 parts of antioxidant, and 5-15 parts of filler.
[0012] As a preferred solution, the mass ratio of the polyether polyol, polyisocyanate and filler is 32-36:20-24:8-13.
[0013] As a preferred solution, the mass ratio of the polyether polyol, polyisocyanate and filler is 33-35:22-24:8-10.
[0014] As a preferred solution, the polyether polyol is polytetrahydrofuran polyol.
[0015] As a preferred embodiment, the number average molecular weight of the polytetrahydrofuran polyol is 2000-3000Da.
[0016] As a preferred solution, the polyisocyanate is at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate and hexamethylene diisocyanate.
[0017] As a preferred solution, the polyisocyanate is diphenylmethane diisocyanate.
[0018] As a preferred solution, the foaming agent is any one of deionized water, pentane, cyclopentane and dichloromethane.
[0019] As a preferred solution, the foaming agent is deionized water or pentane.
[0020] As a preferred solution, the catalyst is at least one of stannous octoate, dimethylethanolamine, dibutyltin dilaurate and triethylenediamine.
[0021] As a preferred solution, the catalyst is stannous octoate.
[0022] As a preferred solution, the stabilizer is at least one of polydimethylsiloxane, polysiloxane copolymer and polysiloxane.
[0023] As a preferred solution, the stabilizer is polydimethylsiloxane.
[0024] As a preferred solution, the flame retardant is aluminum hydroxide.
[0025] As a preferred solution, the antioxidant is antioxidant 1010 or antioxidant 168.
[0026] As a preferred solution, the filler is at least one of talc, calcium carbonate, fumed silica and kaolin.
[0027] As a preferred solution, the filler is a composition of calcium carbonate and fumed silica.
[0028] As a preferred solution, the mass ratio of calcium carbonate to fumed silica is 3-5:0.8-1.4.
[0029] As a preferred solution, the average particle size of the calcium carbonate is 0.1-0.3 μm.
[0030] As a preferred solution, the average particle size of the fumed silica is 20-50 nm.
[0031] As a preferred solution, the raw materials of the sound absorbing layer are, by mass, 20-30 parts of diatomaceous earth, 60-80 parts of latex, 10-20 parts of modified fiber, 3-5 parts of activated carbon, 1-2 parts of silicone oil, and 1-2 parts of crosslinking agent.
[0032] As a preferred solution, the mass ratio of the diatomaceous earth, latex and modified fiber is 20-25:65-75:12-18.
[0033] As a preferred solution, the mass ratio of diatomaceous earth, latex and modified fiber is 22-24:65-70:14-16.
[0034] As a preferred solution, the diatomaceous earth is ultrafine diatomaceous earth; the average particle size of the ultrafine diatomaceous earth is 5-10 μm.
[0035] As a preferred solution, the solid content of the latex is 55-70%.
[0036] As a preferred scheme, the preparation method of the modified fiber specifically includes the following steps: S1: adding short-cut carbon fiber to deionized water and mixing with ammonia water, heating to 60-65°C, adding ethyl orthosilicate and triethanolamine, keeping warm for 1.5-2h, centrifugally filtering and drying after completion, adding to N, N-dimethylformamide, and then adding γ-aminopropylmethyldiethoxysilane and succinic anhydride, heating to 70-80°C, keeping warm for 3-4h, centrifugally filtering after completion, and drying again to obtain pretreated carbon fiber; S2: mixing the pretreated carbon fiber, ferric chloride hexahydrate and 2-aminoterephthalic acid and adding them to N, N-dimethylformamide solution, stirring and mixing evenly, heating to 100-130°C, and keeping warm for 12-16h; S3: after the reaction is completed, naturally cooling to room temperature, centrifuging the product, washing it alternately with N, N-dimethylformamide and deionized water for 3-4 times, and finally vacuum drying it at 70-80°C for 6-8h, and obtaining it after completion.
[0037] As a preferred solution, the mass ratio of the chopped carbon fiber, tetraethyl orthosilicate and triethanolamine is 5-6:1-1.5:0.2-0.4.
[0038] As a preferred solution, the mass ratio of the chopped carbon fibers, γ-aminopropylmethyldiethoxysilane and succinic anhydride is 5-6:0.3-0.5:1.1-1.3.
[0039] The modified fiber added in the present application can effectively improve the mechanical, waterproof and corrosion resistance of the earmuffs, especially the sound-absorbing layer thereof. The added modified fiber can be based on carbon fiber, and after surface group modification, the framework particles are embedded to form a composite fiber structure of points and lines. The existence of this structure can greatly improve the micropore porosity of the sound-absorbing layer, effectively realize the heat conversion of the echo in the micropores, and effectively absorb trace moisture and impurity particles, clear the sound-absorbing obstructing substances inside the sound-absorbing layer, effectively improve the sound absorption effect, and also greatly improve the free resistance and free path of water molecules and active molecules inside the system, thereby maintaining a strong barrier effect on water molecules and active molecules during long-term use, thereby achieving excellent mechanical properties while maintaining excellent waterproof, corrosion resistance and aging resistance.
[0040] As a preferred solution, the mass ratio of the pretreated carbon fiber, ferric chloride hexahydrate and 2-aminoterephthalic acid is 4-4.5:1.5-2:1-1.2.
[0041] As a preferred solution, the average diameter of the chopped carbon fibers is 4-5.5 μm, and the average length is 7.5-10 mm.
[0042] On the other hand, the applicant has found that when the size of the carbon fiber and the raw material ratio of the frame particles are further limited, the waterproof, anti-corrosion and aging resistance of the earmuff sound-absorbing layer can be further improved. The use of chopped carbon fibers of specific sizes controls the aggregation effect of the modified fibers as a whole, thereby enhancing their dispersion effect in the system, and can also effectively reduce the pore size of the micropores occupied by the modified fibers in the system, thereby avoiding the shaking and migration of the modified fibers in the system, thereby maintaining their stability in long-term use, and thus obtaining excellent performance improvement effects.
[0043] As a preferred solution, the average specific surface area of the activated carbon is 1600~2000m2 / g.
[0044] As a preferred solution, the silicone oil is hydrogen-containing silicone oil; the hydrogen content of the hydrogen-containing silicone oil is 1.4-2%.
[0045] As a preferred solution, the cross-linking agent is at least one of dicumyl peroxide, benzoyl peroxide, diethylenetriamine and hexamethylenediamine.
[0046] As a preferred solution, the cross-linking agent is dicumyl peroxide.
[0047] The second aspect of the present application provides a method for preparing the above-mentioned highly flexible and fitted earmuffs, which specifically comprises the following steps: S1: intercepting a mixed fiber of polyester fiber and nylon fiber as an outer protective layer; S2: adding the raw materials of the flexible layer into a high-speed mixer, stirring at a speed of 1000-1500 rpm for 20-25 minutes to ensure that all the ingredients are fully mixed, and quickly pouring the mixed materials into a mold preheated to 40-50°C to ensure that the materials are evenly distributed, closing the mold, placing it in a constant temperature box, setting the temperature to 80-90°C, and maintaining it for 30-40 minutes to allow the materials to be fully foamed and cured, then taking them out, trimming and cutting them to obtain the flexible layer; S3: mixing the raw materials of the sound-absorbing layer, 300-500 Stir at rpm for 15-20 minutes, treat with an ultrasonic defoamer for 10-15 minutes to ensure that there are no obvious bubbles, quickly pour the mixed material into a mold preheated to 40-50°C to ensure that the material is evenly distributed, close the mold, place it in a constant temperature box, set the temperature to 120-140°C, keep it for 50-55 minutes, take it out after curing, and obtain the sound-absorbing layer after trimming and cutting; S4: The outer protective layer, the flexible layer and the sound-absorbing layer are compounded by a hot press at a temperature of 110-120°C and a pressure of 0.3-0.5MPa for 3-5 minutes, and then heated and molded using a customized mold at a temperature of 100-110°C for 5-8 minutes. After completion, trim the edges to obtain the product.
[0048] The beneficial effects of this application are:
[0049] 1. The highly flexible and fitted earmuff provided in the present application not only has excellent sound insulation effect, but also can effectively ensure that it has good moisture resistance, water resistance, aging resistance and mechanical quality. It is especially suitable for environments that require long-term wearing, such as music production, industrial operations and other fields.
[0050] 2. The modified fiber added in the present application can effectively improve the mechanical, waterproof and corrosion resistance of the earmuff, especially the sound-absorbing layer. The modified fiber added can be based on carbon fiber, and after surface group modification, the framework particles are embedded to form a composite fiber structure of points and lines. The existence of this structure can greatly improve the micropore porosity of the sound-absorbing layer, effectively realize the heat conversion of the echo in the micropores, and effectively absorb trace moisture and impurity particles, clear the sound-absorbing obstructing substances inside the sound-absorbing layer, effectively improve the sound absorption effect, and greatly improve the free resistance and free path of water molecules and active molecules inside the system, thereby maintaining a strong barrier effect on water molecules and active molecules during long-term use, so as to achieve excellent mechanical properties while maintaining excellent waterproof, corrosion resistance and aging resistance.
[0051] 3. The highly flexible and fitted earmuffs provided in the present application can further improve the waterproof, anti-corrosion and anti-aging properties of the earmuffs' sound-absorbing layer when the size of the carbon fiber and the raw material ratio of the frame particles are further limited. The use of chopped carbon fibers of specific sizes controls the aggregation effect of the modified fibers as a whole, thereby enhancing their dispersion effect in the system, and can also effectively reduce the pore size of the micropores occupied by the modified fibers in the system, thereby avoiding the shaking and migration of the modified fibers in the system, thereby maintaining their stability during long-term use, and thus achieving excellent performance improvement effects. DETAILED DESCRIPTION
[0052] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0053] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0054] Example 1
[0055] Embodiment 1 provides a highly flexible and fitted earmuff in a first aspect, the structure of which includes an outer protective layer at the top, a sound absorbing layer in the middle and a flexible layer at the bottom.
[0056] The thickness of the outer protective layer is 1.2 mm; the thickness of the sound absorbing layer is 4.5 mm; and the thickness of the flexible layer is 7 mm.
[0057] The outer protective layer is a mixed fiber of polyester fiber and nylon fiber, and the mass ratio of the polyester fiber to the nylon fiber is 1:1.
[0058] The raw materials of the flexible layer, by mass, are: 33.5 parts of polyether polyol, 23 parts of polyisocyanate, 7.5 parts of foaming agent, 1.2 parts of catalyst, 1.5 parts of stabilizer, 4.3 parts of flame retardant, 1 part of antioxidant, and 9.2 parts of filler.
[0059] The polyether polyol is polytetrahydrofuran polyol, purchased from Covestro, a PolyTHF 2000 product with a number average molecular weight of 2000 Da.
[0060] The polyisocyanate is diphenylmethane diisocyanate.
[0061] The foaming agent is deionized water.
[0062] The catalyst is stannous octoate.
[0063] The stabilizer is polydimethylsiloxane purchased from Dow Corning as DC-193.
[0064] The flame retardant is aluminum hydroxide; the antioxidant is 1010.
[0065] The filler is a composition of calcium carbonate and fumed silica, and the mass ratio of the two is 4:1.
[0066] The average particle size of calcium carbonate is 0.2 μm; the average particle size of fumed silica is 25 nm.
[0067] The raw materials of the sound absorbing layer are calculated by weight: 22.5 parts of diatomaceous earth, 68 parts of latex, 15 parts of modified fiber, 3.5 parts of activated carbon, 1.2 parts of silicone oil, and 1 part of cross-linking agent.
[0068] The diatomaceous earth is ultrafine diatomaceous earth; the average particle size of the ultrafine diatomaceous earth is 6 μm.
[0069] The latex had a solid content of 60% and was purchased from a Thai Natural Rubber Company under the model NR Latex 60%.
[0070] The preparation method of the modified fiber specifically includes the following steps, calculated by mass: S1: adding 5.5 parts of short-cut carbon fibers to 180 parts of deionized water and 0.5 parts of ammonia water, mixing and stirring, heating to 65°C, adding 1.4 parts of ethyl orthosilicate and 0.28 parts of triethanolamine, and keeping the temperature for 2 hours. After completion, centrifugation and drying, adding to N,N-dimethylformamide, and then adding 0.4 parts of γ-aminopropylmethyldiethoxysilane and 1.2 parts of succinic anhydride, heating to 80°C, keeping the temperature for 3.5 hours, and completing. After the reaction is completed, centrifuge and filter, and dry again to obtain pretreated carbon fiber; S2: 4.4 parts of pretreated carbon fiber, 1.8 parts of ferric chloride hexahydrate and 1.1 parts of 2-aminoterephthalic acid are mixed and added to 160 parts of N,N-dimethylformamide solution, stirred and mixed evenly, heated to 120°C, and kept warm for 14 hours; S3: After the reaction is completed, it is naturally cooled to room temperature, the product is centrifuged, washed alternately with N,N-dimethylformamide and deionized water for 3 times, and finally vacuum dried at 80°C for 6 hours.
[0071] The chopped carbon fibers had an average diameter of 5 μm and an average length of 8 mm, and were purchased from Jiangxi Shuobang New Materials Co., Ltd.
[0072] The average specific surface area of the activated carbon was 1800 m² / g, and the coconut shell activated carbon products were purchased from Wuxi Maohong Activated Carbon Co., Ltd.
[0073] The silicone oil is hydrogen-containing silicone oil with a hydrogen content of 1.6%, and was purchased from the corresponding hydrogen-containing silicone oil product sold by Foshan Yingzhi Silicone Materials Co., Ltd.
[0074] The crosslinking agent is dicumyl peroxide.
[0075] The second aspect of the present application provides a method for preparing the above-mentioned highly flexible and fitted earmuffs, which specifically comprises the following steps: S1: intercepting a mixed fiber of polyester fiber and nylon fiber as an outer protective layer; S2: adding the raw materials of the flexible layer into a high-speed mixer, stirring at a speed of 1200 rpm for 20 minutes to ensure that all the ingredients are fully mixed, and quickly pouring the mixed materials into a mold preheated to 50°C to ensure that the materials are evenly distributed, closing the mold, placing it in a constant temperature box, setting the temperature to 90°C, and maintaining it for 40 minutes to allow the materials to be fully foamed and cured, then taking them out, trimming and cutting them to obtain the flexible layer; S3: mixing the raw materials of the sound absorbing layer, 400 Stir at rpm for 20 minutes, treat with an ultrasonic defoamer for 12 minutes to ensure that there are no obvious bubbles, quickly pour the mixed material into a mold preheated to 50°C to ensure that the material is evenly distributed, close the mold, place it in a constant temperature box, set the temperature to 130°C, keep it for 55 minutes, take it out after curing, and obtain the sound-absorbing layer after trimming and cutting; S4: The outer protective layer, the flexible layer and the sound-absorbing layer are compounded by a hot press at a temperature of 120°C and a pressure of 0.5MPa for 5 minutes, and then heated and formed using a customized mold at a temperature of 100°C for 6 minutes. After completion, the edges are trimmed to obtain the product.
[0076] Example 2
[0077] The specific implementation of this embodiment is basically the same as that of Embodiment 1, except that the raw materials of the sound absorbing layer are, by mass: 20 parts of diatomaceous earth, 70 parts of latex, 18 parts of modified fiber, 3.2 parts of activated carbon, 1.5 parts of silicone oil, and 1.2 parts of crosslinking agent.
[0078] Example 3
[0079] The specific implementation of this embodiment is basically the same as that of Embodiment 1, except that the raw materials of the sound absorbing layer are, by mass: 25 parts of diatomaceous earth, 65 parts of latex, 12 parts of modified fiber, 3.5 parts of activated carbon, 1.2 parts of silicone oil, and 1 part of crosslinking agent.
[0080] Comparative Example 1
[0081] The specific implementation of this comparative example is basically the same as that of Example 1, except that the raw materials of the sound absorbing layer are, by mass: 30 parts of diatomaceous earth, 60 parts of latex, 25 parts of modified fiber, 3.5 parts of activated carbon, 1.2 parts of silicone oil, and 1 part of crosslinking agent.
[0082] Comparative Example 2
[0083] The specific implementation of this comparative example is basically the same as that of Example 1, except that the raw materials of the sound absorbing layer are, by mass: 25 parts of diatomaceous earth, 80 parts of latex, 5 parts of modified fiber, 3.5 parts of activated carbon, 1.2 parts of silicone oil, and 1 part of crosslinking agent.
[0084] Comparative Example 3
[0085] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified fiber specifically includes the following steps, calculated by mass: S1: 5.5 parts of chopped carbon fibers are added to 180 parts of deionized water and mixed with 0.5 parts of ammonia water, and then heated to 65°C, 0.5 parts of ethyl orthosilicate and 0.11 parts of triethanolamine are added, and the reaction is kept warm for 2 hours. After completion, centrifugal filtration and drying are performed, and then added to N,N-dimethylformamide, and then 0.2 parts of γ-aminopropylmethyldiethoxysilane and 0.6 parts of succinic anhydride are added, and heated to 100 °C. 80℃, keep warm for 3.5h, centrifuge and filter after completion, and dry again to obtain pretreated carbon fiber; S2: add 4.4 parts of pretreated carbon fiber, 1.8 parts of ferric chloride hexahydrate and 1.1 parts of 2-aminoterephthalic acid to 160 parts of N,N-dimethylformamide solution, stir and mix evenly, heat to 120℃, and keep warm for 14h; S3: after the reaction is completed, cool naturally to room temperature, centrifuge the product, wash it alternately with N,N-dimethylformamide and deionized water for 3 times, and finally dry it in vacuum at 80℃ for 6h.
[0086] Comparative Example 4
[0087] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified fiber specifically includes the following steps, calculated by mass: S1: 5.5 parts of chopped carbon fibers are added to 180 parts of deionized water and mixed with 0.5 parts of ammonia water, and then heated to 65°C, 1.4 parts of ethyl orthosilicate and 0.28 parts of triethanolamine are added, and the reaction is kept warm for 2 hours. After completion, centrifugal filtration and drying are performed, and then added to N,N-dimethylformamide, and then 0.4 parts of γ-aminopropylmethyldiethoxysilane and 1.2 parts of succinic anhydride are added, and heated to 100 °C. 80℃, keep warm for 3.5h, centrifuge and filter after completion, and dry again to obtain pretreated carbon fiber; S2: add 2.5 parts of pretreated carbon fiber, 2.8 parts of ferric chloride hexahydrate and 1.9 parts of 2-aminoterephthalic acid to 160 parts of N,N-dimethylformamide solution, stir and mix evenly, heat to 120℃, and keep warm for 14h; S3: after the reaction is completed, cool naturally to room temperature, centrifuge the product, wash it alternately with N,N-dimethylformamide and deionized water for 3 times, and finally dry it in vacuum at 80℃ for 6h to obtain it.
[0088] Comparative Example 5
[0089] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average diameter of the chopped carbon fibers is 7.5 μm, the average length is 15 mm, and the corresponding size products are purchased from Jiangxi Shuobang New Materials Co., Ltd.
[0090] Comparative Example 6
[0091] The specific implementation of this comparative example is basically the same as that of Example 1, except that the short chopped carbon fiber is replaced with glass fiber with an average diameter of 7m and an average length of 12mm, which is purchased from Sichuan Fiberglass Group Co., Ltd.
[0092] Performance Evaluation
[0093] 1. Mechanical properties: The earmuff sound-absorbing layers prepared in the embodiments and comparative examples were subjected to a tensile strength test using a universal tensile tester. The sample size was 1 cm×2.5 cm. The tensile strength at break was recorded when the sound-absorbing layer broke. Each group of embodiments and comparative examples was tested 10 times and the average value was recorded in Table 1.
[0094] 2. Sound absorption performance: The sound absorption performance of the sound absorption layers prepared in the embodiments and comparative examples was tested with reference to standard ISO 354:2003. The test frequency was 250 Hz. Each group of embodiments and comparative examples was tested 10 times and the average value was recorded in Table 1.
[0095] 3. Waterproof performance: The surface waterproofness of the sound-absorbing layer of the embodiments and comparative examples was tested by the sessile drop method. The test water droplet was 3 μL, the test relative humidity was 75%, the test time was 10 min, and the surface water contact angle at 10 min was recorded. Each group of embodiments and comparative examples was tested 10 times and the average value was recorded in Table 1.
[0096] 4. Aging resistance: The sound-absorbing layer prepared in the embodiment and the comparative example was placed in a constant temperature and humidity chamber at a temperature of 62±2°C and a relative humidity of 75±2% for 7 days. The tensile strength was tested using the scheme in performance test 1 before and after the 7-day test. If the retention rate of the tensile strength after the test is ≥95%, it is qualified, otherwise it is unqualified. The retention rate of tensile strength = (tensile strength after the test / tensile strength before the test) × 100%. 50 groups of samples were tested for each embodiment and comparative example, and the qualified rate was recorded in Table 1.
[0097] Table 1 Performance test results
[0098] Example Tensile strength (MPa) Sound absorption performance-sound absorption coefficient Waterproof-water contact angle (°) Ageing resistance qualified rate (%) Example 1 11.7 0.541 104.8 98 Example 2 11.2 0.538 103.2 96 Example 3 10.9 0.533 104.1 96 Comparative Example 1 9.8 0.518 99.4 92 Comparative Example 2 8.2 0.492 84.6 90 Comparative Example 3 9.4 0.501 89.6 92 Comparative Example 4 8.9 0.509 92.3 86 Comparative Example 5 9.1 0.517 90.6 88 Comparative Example 6 9.0 0.493 91.8 84
[0099] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 6 in terms of mechanical properties, waterproof properties, corrosion resistance and aging resistance. This is mainly due to the combined effect of the sound-absorbing layer raw materials, modified fibers and other matching technical solutions specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above performance tests, which further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. A highly flexible and fitted earmuff, characterized in that: Its structure includes an outer protective layer at the top, a sound-absorbing layer in the middle and a flexible layer at the bottom; The thickness of the outer protective layer is 1-2 mm; the thickness of the sound absorbing layer is 3-5 mm; the thickness of the flexible layer is 5-10 mm; The outer protective layer is a mixed fiber of polyester fiber and nylon fiber; The mass ratio of the polyester fiber to the nylon fiber is 1-1.5:1; The raw materials of the flexible layer are, by weight: 30-40 parts of polyether polyol, 20-30 parts of polyisocyanate, 5-10 parts of foaming agent, 1-2 parts of catalyst, 1-2 parts of stabilizer, 3-5 parts of flame retardant, 1-2 parts of antioxidant, and 5-15 parts of filler; The polyether polyol is polytetrahydrofuran polyol; the number average molecular weight of the polytetrahydrofuran polyol is 2000-3000Da; The polyisocyanate is at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate and hexamethylene diisocyanate; The foaming agent is any one of deionized water, pentane, cyclopentane and dichloromethane; The raw materials of the sound absorbing layer are, by weight: 20-25 parts of diatomaceous earth, 65-75 parts of latex, 12-18 parts of modified fiber, 3-5 parts of activated carbon, 1-2 parts of silicone oil, and 1-2 parts of cross-linking agent; The preparation method of the modified fiber specifically comprises the following steps: S1: adding short-cut carbon fibers to deionized water and ammonia water, mixing and stirring, heating to 60-65° C., adding ethyl orthosilicate and triethanolamine, and keeping the temperature for reaction for 1.5-2 hours. After completion, centrifugation and filtration, drying, and then adding to N,N-dimethylformamide, and then adding γ-aminopropylmethyldiethoxysilane and succinic anhydride, heating to 70-80° C., keeping the temperature for reaction for 3-4 hours, after completion, centrifugation and filtration, and drying again to obtain pretreated carbon fibers; S2: pretreated carbon fiber, ferric chloride hexahydrate and 2-aminoterephthalic acid are mixed and added to N,N-dimethylformamide solution, stirred and mixed evenly, heated to 100-130°C, and kept warm for 12-16 hours; S3: after the reaction is completed, the product is naturally cooled to room temperature, centrifuged, washed alternately with N,N-dimethylformamide and deionized water for 3-4 times, and finally vacuum dried at 70-80°C for 6-8 hours. The mass ratio of the chopped carbon fiber, tetraethyl orthosilicate and triethanolamine is 5-6:1-1.5:0.2-0.4; The mass ratio of the chopped carbon fiber, γ-aminopropylmethyldiethoxysilane and succinic anhydride is 5-6:0.3-0.5:1.1-1.3; The mass ratio of the pretreated carbon fiber, ferric chloride hexahydrate and 2-aminoterephthalic acid is 4-4.5:1.5-2:1-1.2; The average diameter of the chopped carbon fibers is 4-5.5 μm, and the average length is 7.5-10 mm; The diatomaceous earth is ultrafine diatomaceous earth; the average particle size of the ultrafine diatomaceous earth is 5-10 μm.
2. The highly flexible earmuff according to claim 1, characterized in that: The mass ratio of the polyether polyol, polyisocyanate and filler is 32-36:20-24:8-13.
3. The highly flexible earmuff according to claim 2, characterized in that: The solid content of the latex is 55-70%.
4. The highly flexible earmuff according to claim 3, characterized in that: The silicone oil is hydrogen-containing silicone oil; the hydrogen content of the hydrogen-containing silicone oil is 1.4-2%.
5. A method for preparing the highly flexible fitting earmuff according to any one of claims 1 to 4, characterized in that: The specific steps include: S1: Cut the mixed fiber of polyester fiber and nylon fiber as the outer protective layer; S2: Add the raw materials of the flexible layer into a high-speed mixer, stir at a speed of 1000~1500 rpm for 20~25min to ensure that all the ingredients are fully mixed, quickly pour the mixed materials into a mold preheated to 40~50°C to ensure that the materials are evenly distributed, close the mold, place it in a constant temperature box, set the temperature to 80~90℃, keep it for 30~40min, allow the materials to fully foam and solidify, then take it out, trim and cut it to obtain the flexible layer; S3: Mix the raw materials of the sound-absorbing layer, 300~500 Stir at rpm for 15-20 minutes, use ultrasonic defoamer for 10-15 minutes to ensure that there are no obvious bubbles, quickly pour the mixed material into a mold preheated to 40-50°C to ensure that the material is evenly distributed, close the mold, place it in a constant temperature box, set the temperature to 120-140°C, keep it for 50-55 minutes, take it out after curing, and trim and cut it to obtain the sound-absorbing layer; S4: The outer protective layer, the flexible layer and the sound-absorbing layer are compounded by a hot press at a temperature of 110-120°C and a pressure of 0.3-0.5 MPa for 3-5 minutes. Then, a customized mold is used for heating and molding at a temperature of 100-110°C for 5-8 minutes. After completion, the edges are trimmed.
Citation Information
Patent Citations
Hot melt adhesive for electronic products and preparation method of hot melt adhesive
CN118813196A
High-fluidity epoxy resin packaging underfill adhesive and preparation method thereof
CN119161839A
Sound absorbing / insulating material
WO2021049224A1